Transmission Lags of Monetary Policy: Probing into Pakistan's Untamed Inflation - Rehman, Muhammad Atiq-ur-; Nasim, Ismat; Ayub, Muahammad; Ibraheem, Ruqayya (iRASD Journal of Economics, 2022)
Monetary policy has been frequently used by many developing countries including Pakistan to curb inflation and smoothen macroeconomic fluctuations. In the near past, it has been observed that monetary tightening has been futile in curbing inflation in many developing economies including Pakistan especially after COVID-19. There is always a time lag before the money supply affects price level or other macroeconomic variables. This study focuses on the transmission mechanism of monetary policy in Pakistan by using monthly data on money supply and inflation for the period 2014:M01 to 2022:M05. After checking stationarity of the series, distributive lag model is estimated using least square method. It is found that there exists a sluggishness in the effectiveness of monetary policy in Pakistan and 4 to 5 months lag exists before the monetary policy exhibits its influence on inflation. It is also noticeable that the lag structure of monetary policy has been changed over time in Pakistan.